2010
DOI: 10.1037/a0018583
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial predictors of employment status among men living with spinal cord injury.

Abstract: Psychosocial variables such as community access, perceived discrimination, social support from significant others, depressive symptoms, and gender identity represent important and understudied predictors of employment status among men living with spinal cord injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 46 publications
2
28
0
1
Order By: Relevance
“…These findings, although preliminary, are consistent with current literature reporting that psychological resources such as affective coping and perceived satisfaction 11,17 are significantly related to vocational activity post SCI. There were also discrepancies between this study and the available SCI literature.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…These findings, although preliminary, are consistent with current literature reporting that psychological resources such as affective coping and perceived satisfaction 11,17 are significantly related to vocational activity post SCI. There were also discrepancies between this study and the available SCI literature.…”
Section: Discussionsupporting
confidence: 82%
“…14,16 In comparison, greater affective impairments, such as depressive symptoms, are suggested to increase the odds of being unemployed. 17 However, methodological and contextual issues confound this literature. First, the psychological measures utilised in the various studies are not necessarily standardised or validated with SCI groups, hence normative data are not available.…”
Section: Introductionmentioning
confidence: 99%
“…And, finally, self-efficacy establishes the confidence and ambition needed to succeed in the face of challenge (Fadyl and McPherson 2010, 73). Indeed, Burns et al (2010) have found that selfreliance and emotional control significantly predicted employment status for people with SCI.…”
Section: Virtues For Success In the Workplacementioning
confidence: 99%
“…En primer lugar, las musculares o esqueléticas (Robb y Mansfield, 2007) que hacen referencia a los dolores lumbares (Issever et al, 2002), a las artritis (Tang, 2010) y a los traumatismos (Wei, 2010). Segundo, las que afectan al sistema nervioso como las lesiones medulares (Burns, 2010) y las cefalalgias (Landy, 2011). Tercero, las que atañen al sistema respiratorio como el asma (Quirce, 2011), la apnea (Ruberto, 2011) y el enfisema (Santo-Tomás, 2011).…”
Section: Introductionunclassified